Reference equations for predicting of handgrip strength in Brazilian middle-aged and elderly subjects (Fisioterapia e Pesquisa, 2009)
The aim of the present study was to evaluate normal values of dominant (D) and non-dominant (ND) upper limb handgrip strength (HGS) in asymptomatic middle-aged elderly subjects and to establish reference equations for predicting HGS. Fifty-four volunteers (51.9% men) aged >;50 years old were enrolled. Weight, height, and both arms circumference were measured, being the body mass index calculated. Mechanical dynamometry was used to measure D-HGS and ND-HGS. Self-reported level of regular physical activity was assessed by Baecke questionnaire. D-HGS was higher than ND-HGS for both sexes and in all age groups (p